Analisis Kinerja Belanja dalam Laporan Realisasi Anggaran pada Dinas Komunikasi Informatika Statistik dan Persandian Kota Cilegon Tahun Anggaran 2021 -2023 - Deasy Femayona Devi (Jurnal Inovasi Bisnis Manajemen dan Akuntansi, 2026)
The Budget Realization Report (LRA) is one of the most essential financial accountability reports. It is the first type of financial report prepared before the balance sheet, operational report, and cash flow statement. Based on the LRA, readers can assess financial performance, particularly through expenditure analysis. The expenditure realization at the Department of Communication, Informatics, Statistics, and Cryptography of Cilegon City in 2021 was relatively low due to the post-COVID-19 recovery phase. In 2022, realization increased significantly due to the implementation of a regional priority program, namely the Smart City initiative. However, in 2023, expenditure realization declined again due to budget rationalization. This study aims to identify and analyze the expenditure performance in the Budget Realization Report (LRA) at the Department of Communication, Informatics, Statistics, and Cryptography of Cilegon City for the fiscal years 2021 2023. This research uses a descriptive quantitative method. The data consists of primary sources derived from the audited Budget Realization Reports (LRA) for fiscal years 2021–2023 and interview results. The analysis techniques employed include: expenditure variance analysis, expenditure growth analysis, expenditure harmony analysis, and expenditure efficiency ratio analysis. The findings of this study show that the expenditure variance ratio is categorized as good, as the realization did not exceed the allocated budget. Expenditure growth was recorded at 21% in 2021, increased significantly to 59% in 2022, and declined to -9% in 2023. The expenditure harmony ratio indicates an average of 87.8% for operational expenditures and 12.14% for capital expenditures. The expenditure efficiency ratio fluctuated, with an average of 85.47%, which is still within the efficient category